Main controlling factors of production and reasonable fracturing scale optimization of deep coalbed methane wells in Shenfu block, Ordos Basin - Lichun SUN; Jia LIU; Na LI; Xinze LI; Heng WEN (Shiyou shiyan dizhi)
The production of deep coalbed methane (CBM) wells in the Shenfu block of Ordos Basin varies greatly, with a lack of understanding of the main controlling factors. To further reveal the production patterns in deep CBM wells, identify key factors affecting well production capacity, and guide the efficient development of deep CBM resources in the Shenfu block, this study analyzed the production dynamic characteristics of typical CBM wells in the area based on basic geological data, production data, and previous research results. Through individual well comparisons and overall trend analysis, the main controlling factors influencing CBM well production in the Shenfu block were identified. The results showed that the gas content and fracturing scale have the greatest impact on production. Pearson's multivariate correlation regression analysis was used to quantitatively evaluate the impact of various factors on production capacity. The factors affecting post-fracturing production capacity of deep CBM wells, ranked by correlation, are as follows: gas content > fracturing sand amount > construction flow rate > fracturing fluid volume > structural depth > thickness. Under certain geological conditions, a reasonable fracturing scale is key to the efficient development of deep CBM wells. An integrated "geological reservoir, fracturing, and economic evaluation" approach was adopted, with economic benefits as the objective. Numerical simulation was conducted to study the coupled optimization of well spacing and fracturing scale. The results determined that the optimal well spacing for the Shenfu block was 300 m, the optimal cluster spacing was 20 m, and the optimal fracture half-length was 120 m. These findings provide technical support for the efficient development of deep CBM resources in the Shenfu block.